Frontal Theta Activity Supports Detecting Mismatched Information in Visual Working Memory - Liang, Tengfei; Hu, Zhonghua; Liu, Qiang (Frontiers in Psychology, 2017)
During the comparison stage of visual working memory processing, detecting the mismatch between the external sensory input and internal representations is a crucial cognitive ability for human, but the neural mechanism behind it remains largely unclear. The present study investigated the role of frontal theta power in detecting the mismatched information in visual working memory in a delayed matching task. A control task required to compare two simultaneously presented visual figures was also designed as a contrast to exclude the possibility that frontal theta activity just reflecting the non-memory-related behavioral conflicts. To better characterize the control mechanisms shaped by the frontal theta oscillation in human visual working memory, colored shapes were adopted as materials while both the task-relevant shape feature and task-irrelevant color feature could be mismatched. We found that the response times of participants were significantly delayed under the relevant- and irrelevant-mismatch conditions in both tasks and the conjunction-mismatch condition in delayed matching task. While our EEG data showed that increased frontal theta power was only observed under the relevant- and conjunction-mismatch conditions in the delayed matching task, but not the control task. These findings suggest that the frontal distributed theta activity observed here reflects the detection of mismatched information during the comparison stage of visual working memory, rather than the response-related conflicts. Furthermore, it is consistent with the proposal that theta band oscillation can act as a control mechanism in working memory function so that the target-mismatched information in visual working memory could be successfully tracked. We also propose a possible processing structure to explain the neural dynamics underlying the mismatch detection process in visual working memory.